Hybrid Video Compression using 2D-DCT and Area Encoding Techniques - Thavamani, U.; Mahesh, Dr.K. (IJRDO -Journal of Computer Science Engineering, 2016)
To store the digital video, even CD/DVD is notsufficient of handling data and therefore, video compressionplays an essential role. Video compression removes theredundant information from digital video without reduce thequality to an unacceptable level. In this proposed work,compressing video is efficiently done by using 2D-DCT which is aversion of DCT with Median filter and Area encoding gives thehigh CR than existing algorithms. In this method, first video isdivided into frames and remove noises using of Median Filter,then that frames are split in to 8x8 pixel blocks. Then 2D-DCT isemployed on these blocks and after that, quantization, zigzagpattern and Area encoding is done on transformed data. Qualityof video is good after compressed the video and also algorithm isfast with less complexity. Experimental results of the proposedwork ensure that effectiveness and gives highest compressionratio without data loss and quality of video.